Talentdiagnostik im Sächsischen Schwimmverband - Sichtung für den kurzfristigen oder mittel- und langfristigen Erfolg? - Altmann, K.; Sperling, W. (Leipziger Sportwissenschaftliche Beiträge, 2013)
The article is based on results of a standardized test procedure to check the versatility (LVT) of swimmers in Saxony. This test arranges itself in the activities of the German Swimming Federation Association (DSV) for talent diagnostics. On the basis of selected results it is scrutinized whether the LVT with its raised eligibility criteria can reflect meaningful the real development process and particularities of the rising talents, as to serve as a basis for reliable eligibility decisions.